Synthesis and evaluation of para-substituted bis(Arylidene)cycloalkanones as potential α-Amylase inhibitor with molecular docking and ADMET profiling - Nur Farah Atiqah Azmi; Mohamad Nurul Azmi; Mahdi Babai; Mohamad Hafizi Abu Bakar; Muntaz Abu Bakar; Mohammad Tasyriq Che Omar (Penerbit Universiti Kebangsaan Malaysia, 2025)
Ten para-substituted bis(arylidene)cycloalkanone derivatives were synthesised, characterised and their inhibitory activities against human pancreatic α-amylase were evaluated. Among them, halogen-substituted derivatives 5d (IC50 = 7.6 ± 1.4 µM) and 5e (IC50 = 6.9 ± 1.8 µM) exhibited superior potency compared to the standard drug acarbose (IC50 = 23.5 ± 2.7 µM). Molecular docking studies indicated that these halogenated derivatives (i.e., compound 5d and 5e) showed a good interaction with human pancreatic α-amylase protein (2QV4) with binding energy of -7.4 ± 0.1 kcal/mol and -7.8 ± 0.1 kcal/mol, respectively, compared with acarbose (-3.9 ± 0.1 kcal/mol). Both of them, form crucial π–π stacking and hydrophobic interactions within the enzyme’s active site residues TYR62 and LEU165. In silico ADMET profiling further supported the favourable drug-likeness, synthetic accessibility, and oral bioavailability of these compounds, making them promising candidates for antidiabetic drug development.